Art and pornography philosophical essays - Maes, Hans, 1975-; Levinson, Jerrold (Oxford : Oxford University Press, 2013)
Do art and pornography overlap, or are the two mutually exclusive? If they are, why is that? 'Art and Pornography' explores the artistic status and aesthetic dimension of pornographic pictures, films, and literature.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Pornography; Erotic art; Sex in art; Pornography -- Philosophy; Art -- Philosophy